Induction motor speed control in closed loop system with thyristor voltage regulator - I. G. Odnokopylov; D. Yu. Lyapunov; N. A. Voronina; A. D. Umurzakova; K. V. Khatsevskiy (Омский научный вестник)
There exists a huge class of actuating mechanisms based on induction motors, where the use of a thyristor voltage regulator is relevant. This paper presents studies on the introduction of the ability not only to reduce the starting current of the motor, but also to regulate the speed of rotation. Studies have been conducted on the possibility of obtaining a regulation range of 1:5 using simulation model. The influence of the resolution of the speed sensor on the accuracy of regulation is investigated. Recommendations on the implementation of the developed method of speed control are given.